2016
DOI: 10.1007/s11682-016-9662-y
|View full text |Cite
|
Sign up to set email alerts
|

The GABAergic system in prefrontal cortex and hippocampus modulates context-related extinction learning and renewal in humans

Abstract: Context-related extinction learning and renewal in humans is mediated by hippocampal and prefrontal regions. Renewal is defined as the reoccurrence of an extinguished response if the contexts present during extinction learning and recall differ. Animal studies implicate hippocampal γ-aminobutyric acid (GABA) A receptors in extinction and renewal. However, human studies on GABAergic mechanisms in extinction learning are lacking. In this fMRI study, we therefore investigated the role of the GABAergic system in c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(26 citation statements)
references
References 60 publications
8
18
0
Order By: Relevance
“…Pronounced context-related activation in hippocampus during extinction and recall is regularly found when comparing REN to NoREN groups in the predictive learning task (Lissek et al, 2013(Lissek et al, , 2016(Lissek et al, , 2018, consistent with studies on fear extinction and recognition tasks that found hippocampal activation necessary for the encoding of context information (Corcoran et al, 2005;Ji and Maren, 2007;Lambert et al, 2017). Bilateral posterior hippocampus activation is frequently observed associated with renewal (Lissek et al, 2013(Lissek et al, , 2016(Lissek et al, , 2018, and lacking activation or deactivation in this region may accompany reduced or lacking renewal (Lissek et al, 2017(Lissek et al, , 2018. Hippocampal activation in the SWITCH group in the present study is consistent with these findings: during extinction and recall in the REG session, where in contrast to the REN group they did not show renewal, their level of hippocampal activity was partially lower than in REN since context processing had a lower priority.…”
Section: Renewal Processing In Hippocampus and Prefrontal Regionssupporting
confidence: 84%
See 3 more Smart Citations
“…Pronounced context-related activation in hippocampus during extinction and recall is regularly found when comparing REN to NoREN groups in the predictive learning task (Lissek et al, 2013(Lissek et al, , 2016(Lissek et al, , 2018, consistent with studies on fear extinction and recognition tasks that found hippocampal activation necessary for the encoding of context information (Corcoran et al, 2005;Ji and Maren, 2007;Lambert et al, 2017). Bilateral posterior hippocampus activation is frequently observed associated with renewal (Lissek et al, 2013(Lissek et al, , 2016(Lissek et al, , 2018, and lacking activation or deactivation in this region may accompany reduced or lacking renewal (Lissek et al, 2017(Lissek et al, , 2018. Hippocampal activation in the SWITCH group in the present study is consistent with these findings: during extinction and recall in the REG session, where in contrast to the REN group they did not show renewal, their level of hippocampal activity was partially lower than in REN since context processing had a lower priority.…”
Section: Renewal Processing In Hippocampus and Prefrontal Regionssupporting
confidence: 84%
“…In contrast, a ratio value of −1 indicates that every response of this type occurred during AAA recall and none during ABA recall, suggesting rather weak memory for AAA extinction associations, with preserved memory for ABA extinction associations, but without context consideration. Higher ratios thus signal a higher probability of genuine renewal (for details on the calculation see Lissek et al, 2017).…”
Section: Renewal Ratiomentioning
confidence: 99%
See 2 more Smart Citations
“…As new learning occurs, subjects will suppress their conditioned response to the previously predictive tone or light. Extinction learning has also been shown to be NMDA receptor dependent 28 , and requires the involvement of hippocampal inhibitory neurons 29 and adult neurogenesis 30 .…”
Section: Introductionmentioning
confidence: 99%